2010
DOI: 10.1002/pssb.201046327
|View full text |Cite
|
Sign up to set email alerts
|

Which electronic structure method for the study of defects: A commentary

Abstract: Phone: þ216 368 6120, Fax: þ216 368 4679 A historic perspective is provided to the choice of methodologies for point defects in semiconductors. A summary and commentary on the highlights of the CECAM workshop: ''Which electronic structure method for the study of defects?'' is given, attempting to provide a link between the different contributions. To this purpose different themes running through the compilation are identified and rather than discussing individual contributions one by one, the discussion is foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 141 publications
2
24
0
Order By: Relevance
“…Around the Si + ion, the electrostatic potential is substantially different from the PC potential because of the finite distribution of the electrons. It, however, becomes almost parallel to the PC potential at a distance of ∼ 2 Å from the ion, and the difference converges to a constant of 2πQ 3L 3 . Therefore, after applying the PC correction and alignmentlike correction, i.e.…”
Section: Potential Alignment Revisitedmentioning
confidence: 97%
See 1 more Smart Citation
“…Around the Si + ion, the electrostatic potential is substantially different from the PC potential because of the finite distribution of the electrons. It, however, becomes almost parallel to the PC potential at a distance of ∼ 2 Å from the ion, and the difference converges to a constant of 2πQ 3L 3 . Therefore, after applying the PC correction and alignmentlike correction, i.e.…”
Section: Potential Alignment Revisitedmentioning
confidence: 97%
“…Despite the importance, it is difficult to directly and fully study point defects by experiments, and first-principles calculations have emerged as an invaluable tool for modeling and understanding the point defects. [1][2][3] In particular, a rapid progress on the computational speed and electronic structure calculation methods as represented by hybrid functionals, quantum Monte Carlo, and the GW approximation allows us to predict the defect properties semi-quantitatively or even quantitatively in recent years. [4][5][6][7][8][9][10][11][12][13] These calculations support and complement experimental findings.…”
mentioning
confidence: 99%
“…The usual approximations of DFT suffer from the infamous band gap problem. There is nowadays a common agreement that the band gap problem particularly plagues DFT predictions of defect properties in semiconductors and insulators 8 . Point defects in non metallic solids generally produce additional electronic levels inside the band gap region.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on this subject can be found in Ref. 9 . A widely used prescription to avoid interactions between the jellium and the system has been proposed by Makov and Payne 10 .…”
mentioning
confidence: 99%